2019
DOI: 10.1021/acs.est.9b00317
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Increases Lead Release to Drinking Water

Abstract: Lead and manganese are regulated in drinking water due to their neurotoxicity. These elements have been reported to co-occur in drinking water systems, in accordance with the metal-scavenging properties of MnO 2 . To the extent that manganese is a driver of lead release, controlling it during water treatment may reduce lead levels. We investigated transport of lead and manganese at the tap in a full-scale distribution system: consistent with a cotransport phenomenon, the two metals were detected in the same co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 83 publications
1
29
1
Order By: Relevance
“…Manganese (Mn) is a common metal in surface and groundwaters, with concentrations typically ranging from 0.001 to 0.2 mg/L, but sometimes exceeding 1 mg/L (World Health Organization, 2004). Its concentration should be limited because (a) Mn discolors water and causes a metallic taste, (b) residual Mn concentrations may be detrimental to children's health (Bouchard, Surette, Cormier, & Foucher, 2018;Dion et al, 2018;Rahman et al, 2015Rahman et al, , 2017, and (c) Mn may increase lead release in distribution systems (Schock, Cantor, Triantafyllidou, Desantis, & Scheckel, 2014;Trueman et al, 2019). In Canada, Mn concentrations are limited to a maximum acceptable concentration of 0.12 mg/L and an aesthetic objective of 0.02 mg/L (Health Canada, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Manganese (Mn) is a common metal in surface and groundwaters, with concentrations typically ranging from 0.001 to 0.2 mg/L, but sometimes exceeding 1 mg/L (World Health Organization, 2004). Its concentration should be limited because (a) Mn discolors water and causes a metallic taste, (b) residual Mn concentrations may be detrimental to children's health (Bouchard, Surette, Cormier, & Foucher, 2018;Dion et al, 2018;Rahman et al, 2015Rahman et al, , 2017, and (c) Mn may increase lead release in distribution systems (Schock, Cantor, Triantafyllidou, Desantis, & Scheckel, 2014;Trueman et al, 2019). In Canada, Mn concentrations are limited to a maximum acceptable concentration of 0.12 mg/L and an aesthetic objective of 0.02 mg/L (Health Canada, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mn oxide deposits within distribution systems have also been found to accumulate or co‐release with other metals including: aluminum (Al) (Friedman et al, 2010; Gerke et al, 2016; Han et al, 2018; G. Li et al, 2018; Triantafyllidou et al, 2019), arsenic (As) (Friedman et al, 2010; Triantafyllidou et al, 2019), chromium (Cr) (Friedman et al, 2010; Gerke et al, 2016), iron (Fe) (Gerke et al, 2016; Han et al, 2018) and Pb (Friedman et al, 2010, 2016; Gerke et al, 2016; Locco et al, 2021). Mn deposits in the distribution system can increase Pb release, either by reduction of less soluble Pb(IV) species to highly soluble Pb(II), or accumulation onto Mn colloidal particles (Brandhuber et al, 2013, 2015; Schock et al, 2014; Trueman et al, 2019). Given recent epidemiologic evidence of synergistic neurodevelopmental effects, co‐occurrence of Mn and Pb release at consumers' taps has an increased public health risk potential.…”
Section: Nature Of Mn In Treated Watermentioning
confidence: 99%
“…This work showed that residual iron and aluminum from coagulation were important contributors to lead release and that natural organic matter also affected lead release. More recently, the CWRS has focused on the benefits of manganese reduction because of its influence on lead release as well as its status as a regulated contaminant (Trueman et al 2019). All of these findings have informed Halifax Water's current corrosion control program, as discussed subsequently.…”
Section: From Research To Policymentioning
confidence: 99%